Development of Science Learning E-Module Equipped with Game On Material Classification of Living Things for Grade VII Students - Arneta Sari; Erda Muhartati; Elfa Oprasmani; Azza Nuzullah Putri (Universitas Islam Negeri Walisongo Semarang, 2023)
This research is a research and development with the ADDIE model. In the media and material validation process carried out by lecturers and teachers using instruments in the form of questionnaires, to measure practicality by teachers and students using instruments in the form of questionnaires, and effectiveness for students was measured using learning outcomes instruments consisting of 20 questions. The results of media development in the form of e-modules, namely the results of the validation of material experts obtained 94%, the validation of media experts obtained 90% in very valid criteria. Then for the implementation results in the form of teacher practice results obtained 96.6%, student practice results obtained 96.91% on very practical features and student effectiveness results obtained at 0.71 including the high category calculated on the N-Gain formula and for classical mastery a proportion 93.10% is obtained with a very effective mixture. Based on the results of the research, it can be interpreted that the science learning e-module is equipped with a game about the classification of practical living things in terms of attractiveness, ease of use, material adjustment and effectiveness in terms of KKM achievement.